Edukasi Perilaku Hidup Bersih Sehat dan Pencegahan Infeksi Saluran Pernapasan Akut Melalui Media Buku Saku Ispa Pada Masyarakat - Manalu, Samuel Marganda H; Bambang, Th. Teddy; Syaputri, Deli (Universitas Islam Negeri Sumatera Utara, 2024)
The impact of unhealthy housing conditions can result in various negative impacts on human health and one of the consequences is ARI. Data obtained in the Sidomulyo sub-district in 2020 showed that there were 206 cases of ARI. And the physical condition of houses in Sidomulyo still does not meet the requirements for a healthy home. People still often spit carelessly, rarely wash their hands with soap, and are less concerned about using masks. The physical condition of the house and community habits are the most important factors in influencing the occurrence of ARI. The purpose of this community service activity is to provide education and training in preventing ARI through pocket books and standing banners about PHBS to the community in Sidomulyo. This activity includes field surveys, coordinating with the head of the health center and the Head of Sudimulyo, education and socialization, training and demonstrations, and handing over pocket books on preventing ARI to the community in Sidomulyo. This service uses education and demonstration methods, evaluation of activities is carried out by assessing the knowledge and abilities of participants by providing pre-post tests both verbally and by demonstration. Community service activities in the form of direct education/counseling have increased knowledge and can be said to be good because the level of knowledge of participants who became counseling participants increased by ≥ 75%, namely 100%.